Evidence for Heterodimerization and Functional Interaction of the Angiotensin Type 2 Receptor and the Receptor MAS. Issue 6 (June 2017) - Leonhardt, Julia; Villela, Daniel C.; Teichmann, Anke; Münter, Lisa-Marie; Mayer, Magnus C.; Mardahl, Maibritt; Kirsch, Sebastian; Namsolleck, Pawel; Lucht, Kristin; Benz, Verena; Alenina, Natalia; Daniell, Nicholas; et al.
Abstract : The angiotensin type 2 receptor (AT2R) and the receptor MAS are receptors of the protective arm of the renin–angiotensin system. They mediate strikingly similar actions. Moreover, in various studies, AT2R antagonists blocked the effects of MAS agonists and vice versa. Such cross-inhibition may indicate heterodimerization of these receptors. Therefore, this study investigated the molecular and functional interplay between MAS and the AT2R. Molecular interactions were assessed by fluorescence resonance energy transfer and by cross correlation spectroscopy in human embryonic kidney-293 cells transfected with vectors encoding fluorophore-tagged MAS or AT2R. Functional interaction of AT2R and MAS was studied in astrocytes with CX3C chemokine receptor-1 messenger RNA expression as readout. Coexpression of fluorophore-tagged AT2R and MAS resulted in a fluorescence resonance energy transfer efficiency of 10.8 ± 0.8%, indicating that AT2R and MAS are capable to form heterodimers. Heterodimerization was verified by competition experiments using untagged AT2R and MAS. Specificity of dimerization of AT2R and MAS was supported by lack of dimerization with the transient receptor potential cation channel, subfamily C-member 6. Dimerization of the AT2R was abolished when it was mutated at cysteine residue 35. AT2R and MAS stimulation with the respective agonists, Compound 21 or angiotensin-(1–7), significantly induced CX3C chemokine receptor-1 messenger RNA expression. Effects of each agonist were blocked by an AT2R antagonist (PD123319) and also by a MAS antagonist (A-779). Knockout of a single of these receptors made astrocytes unresponsive for both agonists. Our results suggest that MAS and the AT2R form heterodimers and that—at least in astrocytes—both receptors functionally depend on each other. Abstract : Supplemental Digital Content is available in the text.